2017
DOI: 10.1002/jso.24910
|View full text |Cite
|
Sign up to set email alerts
|

The RAS mutation status predicts survival in patients undergoing hepatic resection for colorectal liver metastases: The results from a genetic analysis of all‐RAS

Abstract: Approximately half of CLM patients may have a RAS mutation. CLM patients with RAS mutations had a significantly worse survival rate in comparison to patients with RAS wild-type, regardless of the administration of anti-EGFR antibody therapy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(17 citation statements)
references
References 47 publications
0
17
0
Order By: Relevance
“…RAS mutations have consistently been found to be associated with more aggressive tumour biology and are identified in up to 45% of patients with metastatic CRC. For example, the studies published by Amikura et al[ 32 ] and Shindoh et al[ 54 ] both demonstrate that RAS mutational status is associated with significantly worse survival in CRCLM (Amikura et al[ 32 ]: 5-year OS: 42.4% vs 65.3%, P = 0.0006; Shindoh et al[ 54 ]: 3-year DFS 59.9 vs 83.6% P = 0.016). Of note, it has also been reported that among patients put forward for curative intent resection of CRCLMs, the incidence of RAS mutation is only around 10%-15%, indicating that underlying tumour biology, seemingly inseparably linked to PTL, exerts additional prognostic relevance as it appears to indirectly influence surgical candidacy[ 55 ].…”
Section: Discussionmentioning
confidence: 99%
“…RAS mutations have consistently been found to be associated with more aggressive tumour biology and are identified in up to 45% of patients with metastatic CRC. For example, the studies published by Amikura et al[ 32 ] and Shindoh et al[ 54 ] both demonstrate that RAS mutational status is associated with significantly worse survival in CRCLM (Amikura et al[ 32 ]: 5-year OS: 42.4% vs 65.3%, P = 0.0006; Shindoh et al[ 54 ]: 3-year DFS 59.9 vs 83.6% P = 0.016). Of note, it has also been reported that among patients put forward for curative intent resection of CRCLMs, the incidence of RAS mutation is only around 10%-15%, indicating that underlying tumour biology, seemingly inseparably linked to PTL, exerts additional prognostic relevance as it appears to indirectly influence surgical candidacy[ 55 ].…”
Section: Discussionmentioning
confidence: 99%
“…Adam et al 30 Umeda et al 31 Huang et al 32 Mavros et al 33 Viganò et al 34 Connor et al 35 Eefsen et al 36 Schirripa et al 37 Norén et al 38 Sasaki et al 20 Shindoh et al 39 Amikura et al 40 Creasy et al 22 Dupré et al 41 Liang et al 43 Rhu et al 44 Sultana et al 45 Wang et al 46 Yamashita et al 21 Yamashita et al 21 Goto et al 47 Berardi et al 48 Cremolini et al 49 Engstrand et al 50 Goffredo et al 51 lmai et al 52 Koch et al 53 Laengle et al 54 Ledys et al 55 Liao et al 56 Lionti et al 57 Loosen et al 58 Makowiec et al 59 Margonis et al 60 Marques et al 24 Oshi et al 61 Palkovics et al 62 Shigematsu et al 63 Vallance et al 64 Wang et al 23 Wang et al 65 Zheng et al 66 Prediction interval 0·1 0 ·5 1 2 10…”
Section: Fig 2 Forest Plots Showing Impact Of Primary Tumour Locatiomentioning
confidence: 99%
“…Partelli et al 29 Connor et al 35 Eefsen et al 36 Schirripa et al 37 Sasaki et al 20 Shindoh et al 39 Amikura et al 40 Creasy et al 22 Heise et al 42 Wang et al 46 Yamashita et al 21 Yamashita et al 21 Goto et al 47 Berardi et al 48 Cremolini et al 49 lmai et al 52 Laengle et al 54 Ledys et al 55 Lionti et al 57 Margonis et al 60 Marques et al 24 Oshi et al 61 Shigematsu et al 63 Wang et al 23 Zheng et al 66…”
Section: Referencementioning
confidence: 99%
“…Currently, some molecular biologic markers are being used to guide therapy and prognostication in patients with CRLM. RAS mutations are found in 15-45% of colorectal cancer patients, and are associated with poor overall survival (OS) and recurrence-free survival (RFS) after liver resection 4 - 6 . A previous study found that the addition of RAS mutation status to create a modified clinical score (m-CS) could outperform the t-CS in predicting survival after resection of CRLM 7 .…”
Section: Introductionmentioning
confidence: 99%